2009
DOI: 10.2174/156802609789630820
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery and Quantification of Unformulated Interfering RNAs In Vivo

Abstract: Synthetic small interfering RNAs (siRNAs) open promising new therapeutic perspectives in acute and chronic pathologies. A number of experiments in mice demonstrated the ability of naked siRNAs injected under a normal pressure to trigger gene silencing in vivo, translating into a measurable phenotype. We focus in this review on the information that we can gain from these experiments, and discuss how the specificity of the gene silencing in vivo can be controlled. Because the activity of most drugs increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 122 publications
(161 reference statements)
1
22
0
Order By: Relevance
“…Because of this, the total siRNA in tissues does not always correlate with efficacy (Abrams et al 2010). Imaging analysis may yield relevant information on subcellular siRNA delivery, but it is not always precise in quantification and it cannot distinguish between intact siRNA and the free labels released from siRNA by metabolism (Morin et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the total siRNA in tissues does not always correlate with efficacy (Abrams et al 2010). Imaging analysis may yield relevant information on subcellular siRNA delivery, but it is not always precise in quantification and it cannot distinguish between intact siRNA and the free labels released from siRNA by metabolism (Morin et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Human clinical trials using synthetic siRNA started in 2004 (Soutschek et al 2004), and a list of ongoing clinical trials applying siRNA was summarized (Morin et al 2009). The first siRNA clinical trial that used a targeted nanoparticle delivery system was reported (Davis et al 2010) in which a human transferrin protein targeting ligand was displayed on the exterior of a polymer nanoparticle to engage transferrin receptors of patients with melanoma after systemic administration.…”
mentioning
confidence: 99%
“…43 The mechanisms for greater uptake of siRNA into tissue cells in vivo, compared with ineffectiveness in cultured cells, are not known, but could involve serum proteins or components of the complex extracellular matrices in tissues. 43 However, peptide C6M3 and C6M6 as carrier for siRNA could promote the antitumor effect further and provide better protection against enzymatic degradation. On day 27, mice were sacrificed and tumor tissues were excised (Figures 5c and 5d).…”
Section: Resultsmentioning
confidence: 99%